(untitled) (Studia Prawnicze / The Legal Studies, 1980)
Dynamic economic developement in People’s Poland, industrialization of the country and the resulting changes in the structure of population as well as big urban aglomerations and new towns, caused with particular sharpness the need to discuss the issue of rational administration of the land in the towns, constituting one of basic elements of planned building and construction on the lands within the town limits. Carrying out of spatial planning in towns depends to a considerable degre, upon significant level of freedom in dealing with the land designated for construction and also upon proper application of these legal institutions which enable acquisition of such land by the state. Statutory right of pre-emption belonging to the state (TReasury) is one of such institutions, regulated in the law of July, 14, 1961 on administration of the land in towns and settlements (uniform test in the Journal of Laws of 1969 n° 22 entry 159 with later changes). The purpose of this article is to present some fundamental issues concerning statutory right of pre-emption belonging to the State (Treasury) within the te’,7.’1L limits. In particular, the Author discusses the character of such right, its social-economic significance for the whole spatial planning in the towns, its scope and possibilities of enforcement both from objective and subjective point of view. These are the matters dealt with in chapter two and three of this article. As far as the subject-matter of statutory right of pre-emption belonging to the Treasury is concerned, numerous arguments of both legal and socio-economic character were cited against making perpetual usufruct and separate ownership of living quarters subject to this Tight. Chapter four discusses the relation between administrative and civil law procedures and acts. In this chapter the following issues were presented; 1) ciljracter of acts of administrative organ before declaring the will to enforce the right of pre-emption, in particuar in connection with the reform of local administration. of 1975, 2) civil-law consequences of an administrative act, 3) the scope of judiciary control of enforcements of the right of pre-emption. According to the Author’s opinion in present legal situation, acts undertaker! by the organs of administration and aimed at enforcement of the right of pre-emption do not result in an administrative decision, nor can they de considered so called „inner acts of administration". Thus, de lege ferenda, the Author suggests that a civil law declaration of will made by administrative organ should be preceded by a decision of this organ subject to the, provisions of the code of administrative procedure. Chapter five deals with other legal issues connected with the enforcement of statutory right of pre-emption. In particular, the following issues are discussed here; the term specified by the law for the enforcement of the right of pre-emption, its form, the notification of seller of the fact that a declaration of will to enforce the right of pre-emption by an administrative organ was made, consequences of unconditional sale, enforcement of the right of pre-emption in executive proceedings. In the final, sixth chapter, legal issues connected with the renouncement of the right of pre-emption by the Treasury are discussed. In particular the Author concentrates on the differences between the situation, in which the Treasury renounces its right of pre-emption in a specific case by way of non-enforcement of this right during the 3-months period or by way of a spearate declaration of will made before the above-mentioned period, and in the situation in which the declaration of renouncement is made after the enforcement of the right took place.